A comparison of knowledge and attitudes about snakes among urban and rural middle school students in the metropolitan area of Pachuca, Hidalgo - Reyes-Resendiz, Suri Shaddai; Fernández Badillo, Leonardo; Zuria Jordan, Iriana (Acta Universitaria, 2026)
Humans see snakes as dangerous animals and do not know much about their biology, but environmental education can help to change this thinking. The objective of this study is to compare the knowledge and attitude about snakes among students from two urban and two rural middle schools in the Metropolitan Zone of Pachuca, Hidalgo. Four different questionnaires were applied in two stages: before and after teaching environmental education activities (EEA), and the results were analyzed by calculating percentages. It was found that students in rural schools recognized more native species than those in urban schools; however, they were more afraid of snakes and did not know much about their biology. It was evident that the EEA  helped change students’ attitude towards snakes, making it an effective tool for transmitting knowledge, eliminating erroneous beliefs and unfounded fears, as well as promoting their conservation.